Mathematical Literacy in Statistics Following Differentiated Learning Using Outdoor Modeling Mathematics - Kaivida Novi Yosita Aritonang; Sofnidar Sofnidar; Dewi Iriani (Education and Talent Development Center Indonesia (ETDC Indonesia), 2026)
Indonesia’s students continue to show low literacy and numeracy performance. In PISA, Indonesia ranked 68th out of 81 countries with a mathematics score of 379. This study describes eighth-grade students’ mathematical literacy in statistics after differentiated learning implemented through the Outdoor Modeling Mathematics (OMM) model. The study was conducted at SMPN 5 Pelepat Ilir in May 2025 using a qualitative descriptive design. Six students were selected purposively from a class of 33 based on learning readiness: high (S1KBT, S2KBT), moderate (S1KBS, S2KBS), and low (S1KBR, S2KBR). Data were collected through a mathematical literacy test and semi-structured interviews and were analyzed using three literacy processes: formulating situations mathematically, employing mathematical concepts, facts, procedures, and reasoning, and interpreting and evaluating mathematical results. The findings show that all six students met the three processes, indicating a high level of mathematical literacy after the intervention.